2013
DOI: 10.1111/jac.12028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Temperatures on Spikelet Fertility in Different Rice Cultivars based on Temperature Gradient Chamber Experiments

Abstract: Spikelet sterility in rice (Oryza sativa L.) induced by high temperatures is a major concern given global warming predictions. We studied differences among eight rice cultivars in spikelet fertility at five different temperature levels in temperature gradient chamber (TGC) experiments. Six japonica and two indica cultivars were exposed to high-temperature gradients in TGCs during the 2005 flowering season. Spikelet sterility increased with temperature in TGCs and differed among cultivars because of both variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
2
47
1
1
Order By: Relevance
“…Accurate temperature data are essential for these purposes (Fukuoka and Yoshimoto 2012), since crop productivity and quality are sensitive to temperature (e.g. Morita 2008;Maruyama et al 2013 for paddy rice).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate temperature data are essential for these purposes (Fukuoka and Yoshimoto 2012), since crop productivity and quality are sensitive to temperature (e.g. Morita 2008;Maruyama et al 2013 for paddy rice).…”
Section: Introductionmentioning
confidence: 99%
“…In the Japonica cultivars, Akita-komachi and nipponbare (Maruyama et al, 2013;Matsui et al, 2001), Hitomebore (Maruyama et al, 2013), and Todorokiwase (Tenorio et al, 2013) are classified as considerably heat-tolerant genotypes. In Indica cultivars, IR24 and IR36 (Maruyama et al, 2013), Ciherang, AdT36, increase when panicles are exposed to high temperatures during grain filling. Chalky grains induced by heat stress are associated with reduction in head rice yield and market values.…”
Section: Genetic Variation In Heat Tolerance At Flowering and Flower mentioning
confidence: 99%
“…Rice is most susceptible to heat stress at flowering, and previous chamber experiments showed that temperatures above 32-36 °C cause high spikelet sterility (Jagadish et al, 2008;Matsui et al, 1997aMatsui et al, , 1997bMatsui et al, , 2001Maruyama et al, 2013;Prasad et al, 2006;Satake & Yoshida, 1978;Weerakoon et al, 2008). Heat-induced spikelet sterility (HISS) at flowering is associated with reduction in grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was conducted using TGCs, as reported in our previous studies (Hamasaki et al, 2010;Maruyama et al, 2013), to expose rice plants to different temperatures. The TGCs at KO-ARC are pipe-framed greenhouses (3.6 m width × 3.0 m height × 30 m length) covered with 0.1-mm-thick polyolefin film (TokanAce-N; Tokan Kosan, Tokyo, Japan).…”
Section: Experiments 1: Effects Of High Temperatures Before Headingmentioning
confidence: 99%
“…The timing of panicle emergence in rice plants is a key trait in an agronomic sense, as it determines the flowering season and the beginning of the ripening phase, and consequently affects grain filling and yield formation based on climatic conditions after flowering. Therefore, the timing of panicle emergence, or flowering, in rice has been studied extensively from diverse viewpoints, such as breeding and genetics (Yano et al, 1997;Nakagawa et al, 2005), anthesis and fertilization (Prasad et al, 2006;Mohammed et al, 2011;Tanaka et al, 2014), and climatic responses and phenology (Yin and Kropff, 1996;Tao et al, 2006;Wakiyama et al, 2013).…”
Section: Introductionmentioning
confidence: 99%